Laboratory disinfects as preservatives for Helicoverpa armigera nucleopolyhedrovirus - Sireesha, K.; Kumar, C.S.; Ranga Rao, G.V.; Rao, P.A.; Kumar, L. (2008)
Bacterial contamination is an important setback in large scale production of nucleopolyhedroviruses (NPV). Hence, attempts were made to decrease the bacterial contamination in storage using different commonly used laboratory disinfectants. The studies revealed that all the preservatives tried could effectively reduce the bacterial contamination and the associated bad odour problem in storage. Helicoverpa NPV samples with all the preservatives studied gave -90% mortality under laboratory bio-assays after a period of two months of storage. The samples which are stored in acetone and ethyl alcohol, gave 73.3 and 70%- mortality, respectively after 10 months storage cost of different preservatives ranged from Rs.3.0-12.5 ha-1, which is affordable.